Peri-articular injection of an analgesic mixture in primary total hip arthroplasty: an effective strategy for pain control during the first post-operative day (2018)
Background Previous studies of soft tissue infiltration in hip arthroplasty present variable results. The purpose of this study is to identify whether injection of an analgesic mixture improves pain management during the immediate post-operative period. Materials and methods This cohort study compared 129 patients that received peri-articular soft tissue injection with 20 ml of 0.25% bupivacaine and 2 ml of ketorolac (30 mg/1 ml) in 28 ml of saline solution, with 71 patients who did not received injections. Pain intensity in the Verbal Analog Scale (VAS), opioid titration, and consumption (mg morphine equivalents) in the post-anaesthetic care unit (PACU) and during the first post-operative day were assessed for both groups. All patients received the same analgesia protocol. Results Median VAS score in the PACU was 4 (IQR 2–7) in the injection group and 7 (IQR 4–8) in the non-injection group (p = 0.001). Median opioid titration was 0 mg for the injection group and 2.6 mg for the non-injection group (p = 0.011). In the first post-operative day, the difference in VAS scores between groups was statistically significant (p = 0.009), but there was no difference in opioid consumption. Conclusion Soft tissue injection with local anesthetics and non-steroidal anti-inflammatory drugs allows adequate pain control in the immediate post-operative period and reduces the requirement for opioid consumption. We recommend the implementation of this safe and effective strategy in post-operative pain management after primary hip arthroplasty.